The process of the university youths' training on gender education and civic values - Belkis Luisa Aranda Cintra; Irela Paz Domínguez; Graciela Ramos Romero; Yamilet Ávila Seco; Delfina Durán Rengifo (Centro Provincial de Información de Ciencias Médicas, 2017)
Culture is the result of the apprehension by the individual of the influences of each context where the social and cultural identity manifestations are established and besides, those of gender, derived from the training processes in several institutions.  Universities in Cuba have the commitment of training men with a high professional and general culture that allows them to adopt a transforming attitude when facing the challenges of the new society and responsible behaviors in all the spheres of the life; however, according to observations, exchanges and professional practice, appropriate behaviors are not always exposed, so that some considerations regarding the expression of gender identity and the civic values are exposed in this work, as results of the assimilation of rules settled down in the environment where the university students are trained.